Late follow‐up of the randomized radiation and concomitant high‐dose intra‐arterial or intravenous cisplatin (RADPLAT) trial for advanced head and neck cancer. (6th July 2015) - Heukelom, Jolien; Lopez–Yurda, Marta; Balm, Alfons J. M.; Wijers, Oda B.; Buter, Jan; Gregor, Theo; Wiggenraad, Ruud; de Boer, Jan Paul; Tan, I. Bing; Verheij, Marcel; Sonke, Jan‐Jakob; Rasch, Coen R.
ABSTRACT: Background: The radiation and concomitant high‐dose intra‐arterial or intravenous cisplatin (RADPLAT) phase III trial compared intra‐arterial (IA) to intravenous (IV) cisplatin‐based chemoradiation for head and neck cancer. Long‐term efficacy and toxicity are reported after a median follow‐up of 7.5 years. Methods: Patients with inoperable squamous cell carcinoma (SCC) of the oropharynx, oral cavity, or hypopharynx, were randomized between radiotherapy (RT) + IA cisplatin 150 mg/m 2, followed by systemic rescue or RT + I.V. cisplatin 100 mg/m 2 . RT consisted of 46 Gy to the affected and elective areas, followed by a boost of 24 Gy. Results: Among 237 patients, 57 recurred locally, 35 regionally, and 80 locoregionally. There were 32 second primary tumors, 65 distant metastases, and 154 deaths. Locoregional control and overall survival were not different between the treatment arms. Late dysphagia was worse in the I.V. arm (log‐rank p  = .014). Conclusion: IA cisplatin did not improve tumor control compared to I.V. administered cisplatin, despite the higher dose in IA delivery of the drug. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E488–E493, 2016